University students’ social contact with Chilean indigenous people: structure and associations with stereotypes - Salazar-Fernández, Camila (2024)
In non-indigenous Chilean university students, this study examined (1) the two-dimensional structure (quantity and quality) of social contact with the Mapuche people, and (2) the associations of these dimensions with stereotypes attributed to this group in a context of interethnic conflict. A purposive sample of 332 participants reported on their contact with the Mapuche, both in quantity and quality, and their adherence to various positive and negative stereotypes about this outgroup. The results supported an oblique factorial structure of contact (quantity and quality), revealing significant correlations between these factors and the stereotypes. Importantly, the quality of contact demonstrated more intense associations with stereotypes compared to its quantity. The latent interaction between quantity and quality did not significantly impact stereotypes. The study highlights the need to differentiate quantity and quality of contact when examining their relationships with other psychosocial constructs.